2022
DOI: 10.1503/cjs.020719
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for Canadian bariatric surgical and medical centres: a statement from the Canadian Association of Bariatric Physicians and Surgeons

Abstract: Summary The goal of this statement is to offer standardization in bariatric care across Canada, to provide patients with optimal access to obesity treatment and potentially improve outcomes by reducing complications, length of hospital stay and readmission rate. The definition of Canadian standards also aims to promote a comprehensive, multidisciplinary approach to patients with obesity, to define the minimal qualifications for surgical and medical training and to offer credentialling for bariatric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…In addition to SG, several other types of bariatric–metabolic procedures (including RYGB and one anastomosis gastric bypass) are performed at our institution. Based on the annual number of bariatric-metabolic procedures, our institution’s bariatric center is currently considered a Level II bariatric center [ 17 ]. Preoperatively, all patients underwent a standard workup, including history, physical examination, and an extensive laboratory/imaging evaluation (blood tests, esophagogastroduodenoscopy, polysomnography, abdominal ultrasound, heart ultrasound, etc.).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to SG, several other types of bariatric–metabolic procedures (including RYGB and one anastomosis gastric bypass) are performed at our institution. Based on the annual number of bariatric-metabolic procedures, our institution’s bariatric center is currently considered a Level II bariatric center [ 17 ]. Preoperatively, all patients underwent a standard workup, including history, physical examination, and an extensive laboratory/imaging evaluation (blood tests, esophagogastroduodenoscopy, polysomnography, abdominal ultrasound, heart ultrasound, etc.).…”
Section: Methodsmentioning
confidence: 99%
“…With the aid of the anesthesiologist, a bougie is then inserted trans orally, that will be used to guide the resection. Current consensus states that a 36 Fr size bougie is the most widely used [ 17 , 18 , 19 , 20 ], with multiple bougie sizes being reported as preferred in the literature. As standard practice, we used a narrower, 32 Fr bougie for the creation of the gastric sleeve.…”
Section: Methodsmentioning
confidence: 99%
“…The results of this study have important clinical implications. First, these models will provide a clearer understanding of the role the exercise professional in the bariatric surgery setting provides and the value they bring to a multidisciplinary surgery team, including nurses (125,129,130). More practically, findings provide practical and useful information that could contribute in four major areas: 1) describing the roles and responsibilities exercise professionals are able to fill, helping create job descriptions, 2) developing CPT/billing codes for reimbursement (aligning with how cardiac rehab was developed), helping to spur other funding for positions, 3) credentialing exercise professionals in bariatric care and development of "core competencies" (119) and 4) helping to coordinate care of clinical exercise personnel, perhaps in a system of ExerciseCare.…”
Section: Issues In Bariatric Exercise Surveymentioning
confidence: 99%
“…Thirteen sources reported study findings concerning the validity and/or accuracy of BMI as a measure of obesity [14][15][16][17][18][19][20][21][22][23][24][25][26] and are summarized in Table 2; 13 sources reported findings regarding the use of BMI as a surgical cut-off and are summarized in Table 3; [27][28][29][30][31][32][33][34][35][36][37][38][39] 5 reported ethical issues related to BMI [40][41][42][43][44] and are summarized in Table 4; and 3 guidelines were identified describing recommendations related to the use of BMI as a threshold or cut-off in determining eligibility for surgery (summarized in Table 5). [45][46][47] With regard to validity and/or accuracy, most of the included studies either compared BMI to other measures of obesity and/or adiposity, or investigated the effects of BMI cut-offs for surgical eligibility on surgical outcomes. Most studies either found discrepancies between BMI and other measurements or concluded that there was insufficient evidence to support BMI cut-offs for surgical eligibility.…”
Section: Annotated Reference List Overall Summarymentioning
confidence: 99%